A lei das leis : notas sobre o contexto de produção da Constituição de 1911 - Alves, Jorge Fernandes (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The present text aims at evaluating the context of production of the text of the 1911 Constitution, addressing the discussion that took place at the Constituent Assembly around the most important topics.